Literature review : critical risk factors affecting information-technology projects - Sorooshian, Shahryar; Mun, Sam Yin (Romanian Society for Quality Assurance - SRAC, 2020)
Information technology (IT) projects do not only function as a business platform for launching new business direction, but can also simultaneously increase the profit and market value of the industry. In general, many of the implemented IT projects are accompanied by countless risks that might be difficult for the project manager to manage and mitigate. As such, the project manager is often faced with the mammoth task of making a prognosis on the potential risks that may threaten the implementation of a unique, complex or/and large-scale IT project. Hence, by reviewing existing literature, this study had aimed to concentrate on the critical risk factors faced by the IT projects as a way of aiding the project manager in mitigating the current management issues.